Tehran-Riyadh Détente 2023: Implications for Pakistan - Attiq-ur-Rehman (ASIAN Journal of International Peace & Security (AJIPS), 2023)
The recently signed Iran-Saudi deal has generated a new debate in the contemporary global power politics because the role of China mediating a deal between to archrival nations has surprised the whole world. The Western powers are now compelled to alter their ongoing models of Middle Eastern policies while recognizing China as an important factor in affecting the mainstream geo-strategic calculations of the great powers. In this debate, the position of Pakistan cannot be ignored because Islamabad has a decades-long rivalry with New Delhi parallel to having multileveled relations with Beijing. Additionally, the ideological affiliations of Islamabad with the main power centers of the Muslim world have raised the significance of this development for Pakistan. This deal has significant implications for the politics of the Middle Eastern and South Asian regions, and both are the main points of Pakistan’s foreign policy. Thus, this paper seeks to provide a descriptive account of various arguments related to the ongoing politics of South Asian and Middle Eastern regions in the post-deal environment. It is an academic endeavor to align Pakistan with the changing attributes of the Muslim world, where China has been recognized as an influential player and a potential force for shaping new political scenarios. This study is based on a combination of explorative and analytical method whereas its theoretical description has been maintained with the support of Hegemonic Stability Theory (HST).